Roots of social sensibility and neural function - Schulkin, Jay. (Cambridge, Mass. : MIT Press, 2000)
We are social animals, with evolved mechanisms to discern the beliefs and desires of others. This social reason is linked to the concept of intentionality, the ability to attribute beliefs and desires to others. In this book Jay Schulkin explores social reason from philosophical, psychological, and cognitive neuroscientific perspectives. He argues for a pragmatist approach, in which the role of experience--that is, interaction with others--is central to any consideration of action in the social world. Unlike some philosophers of mind, Jay Schulkin considers social reason to be a real feature of the information processing system in the brain, in addition to a useful cognitive tool in predicting behavior. Throughout the book, he incorporates neurobiological evidence for a domain-specific system for social cognition. Topics covered include the centrality of intentional attribution to social cognition, the rise of cognitive science in the twentieth century, the functional argument for the role of experience, intentional understanding in nonhuman primates, theory of mind and natural kinds in children, autism as a disorder of theory of mind, and the integration of emotions into theory of mind.
1. Intentionality and social sensibility -- 2. Cognitive and neural sciences -- 3. Experiments on social reasoning in primates -- 4. Development of social reason in children -- 5. Autism -- 6. Social reason and action.
"A Bradford book."
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Cognition -- Social aspects; Cognition and culture; Human information processing -- Social aspects; Psychology, Comparative; Cognition; Cognition; Psychology, Comparative; Cognition -- Aspect social; Cognition et culture; Traitement de l'information chez l'être humain -- Aspect social; Psychologie comparée.; Cognition; cognition; SCIENCE -- Cognitive Science; PSYCHOLOGY -- Cognitive Psychology; Cognition; Cognition and culture; Cognition -- Social aspects; Human information processing -- Social aspects; Psychology, Comparative; COGNITIVE SCIENCES/General; NEUROSCIENCE/General